Evaluation of total hip arthroplasty and comparing the effect of different types of anesthesia. - Mahdi Abed Hussein; Anass Jafar Abd Almunim Alsudani; Allawi Hameed Kareem (Genius Journals, 2022)
This study aimed to Evaluation of total hip arthroplasty and comparing the effect of different types of anaesthesia A survey was conducted in different Hospitals in Iraq, where 100 patients were collected to those who underwent hip replacement, and they were relied on regional and general anaesthesia. the patients were distributed to 50 patients who underwent general anesthesia, including 40 male patients, ten women, and 50 patients who underwent regional anesthesia. The most common complications of anaesthesia, especially in the case of elevated obstruction, are arterial hypotension and bradycardia due to the rapid development of sympathetic blockade. For this reason, in hip arthroplasty for spinal anesthesia, 0.5% elevated pressure or isobaric pressure is often used
Keywords: Anaesthesia; PVD; total hip; BMI